2009
DOI: 10.1007/s12192-009-0099-8
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ASK1 expression during overexpression of Trx and HSP70 in stressed fish liver mitochondria

Abstract: Mitochondrial heat shock protein 70 (mtHSP70) is found to play a primary role in cellular defense against physiological stress like exposure to environmental contaminants and helpful in the maintenance of cellular homeostasis by promoting the cell survival. In the present investigation, the environmental-stress-induced increase in mtHSP70 levels along with the quantification of apoptosis signal regulating kinase 1 (ASK1) and thioredoxin (Trx) were measured in the liver mitochondria of grey mullets (Mugil cepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For example, Cu, Cd, Pb, and Zn were found to induce the expression of hsp70 in fathead minnow, yellow perch, and rainbow trout [51e54]; arsenite and the herbicide oxyfluoren are known to stimulate hsp70 expression in salmon and the Egyptian Nile fish [55,56]. In addition, oxidative stress has also been found to affect hsp70 expression in some fish species [57,58]. In our study, we found that SoHsp70 expression was significantly upregulated by challenges with Fe, Cu, Hg, and H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cu, Cd, Pb, and Zn were found to induce the expression of hsp70 in fathead minnow, yellow perch, and rainbow trout [51e54]; arsenite and the herbicide oxyfluoren are known to stimulate hsp70 expression in salmon and the Egyptian Nile fish [55,56]. In addition, oxidative stress has also been found to affect hsp70 expression in some fish species [57,58]. In our study, we found that SoHsp70 expression was significantly upregulated by challenges with Fe, Cu, Hg, and H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Stress biomarkers heat shock protein 70 kDa (Hsp70), total ubiquitin (Ub), and total antioxidant capacity (TAC) were then quantified. These biomarkers were selected due to their important roles in cellular stress responses of organisms to environmental challenges and thermal adaptation: (i) Hsp70 is a chaperone that stabilizes degrading proteins ( Jolly et al, 2018 ); (ii) Ub signals irreversibly damaged proteins for degradation in the proteasome ( Madeira et al, 2014 ) and TAC quantifies both enzymatic and non-enzymatic antioxidants, which indicates the ability to counteract oxidative stress-induced damage in cells ( Padmini and Geetha, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, treatment of monocytes, fibrosarcoma, and endothelial cells with Trx1 induced the expression of TNF, IL-1, IL-6, IL-2, and IL-8 (Schenk et al 1996;Padmini and Rani 2010). In teleost, immune-regulatory property has only been found in the Trx of flathead mullet, which modulates the activity of apoptosis signal-regulating kinase 1 and cJun NH2-terminal kinase 1/2 (Takeda et al 2003;Padmini and Vijaya Geetha 2009). In our study, we examined whether rCsTrx1 had any effect on the expression of the immune genes that so far have been identified in tongue sole.…”
Section: Effect On Immune Responsementioning
confidence: 99%